Alternatives for the End of the World: Myth, Tragic Destiny and Science Fiction - Pérez-Amezcua, Luis Alberto; Junco, Ethel (Amaltea. Revista de Mitocrítica, 2020)
We propose a reading of Terminator: Dark Fate, the most recent installment of one of the most influential film sagas of contemporary science fiction, and we contrast it with the sense of the classic tragic destiny of The Trojans, by Euripides. From the configuration of the mytheme of the protective mother in the two protagonists (Hecuba / Sarah Connor), we stand out the mythemes that function as links between both protagonists. Respecting the properties of each genre, we observe that the woman-mother figure has an active position facing destiny with which she defines her heroic type and the fate of her community. We conclude stating that the mytheme’s efficacy that sustains the filmic text it is based more on the mythical paradigm than on the scientific one.